If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -3x = 6 + 2x Solving 14 + -3x = 6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 14 + -3x + -2x = 6 + 2x + -2x Combine like terms: -3x + -2x = -5x 14 + -5x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 14 + -5x = 6 + 0 14 + -5x = 6 Add '-14' to each side of the equation. 14 + -14 + -5x = 6 + -14 Combine like terms: 14 + -14 = 0 0 + -5x = 6 + -14 -5x = 6 + -14 Combine like terms: 6 + -14 = -8 -5x = -8 Divide each side by '-5'. x = 1.6 Simplifying x = 1.6
| 2-6x=62 | | -3-4x=37 | | 14+3j=43 | | 4y-8+y+25=8y+20-6y | | 8(x-1)+4=9+7x | | 8x=7y+9 | | 12x^2+16x-28=0 | | 5x+4=44 | | 7g+12=9g-6 | | 3(2x-2)=4x | | 6x-1=41 | | 3(h-4)+5=60 | | 13x+2x=-150 | | 5m+42=11m | | (4x)*2=16 | | 5(8x-4)=44x | | 2-(x+5)=4x-8 | | 3(x+8)=33 | | 6(6n+7)=7(6n+6)+5 | | 7x-x=36 | | 5w+10=0 | | 6x-5y=9 | | 16(x+2)=4(4x+1)+28 | | -20y=120 | | 6x=32-2x | | 40=18x-10x | | -3(x+5)+5x=10 | | 10x^2+7x-5=0 | | 6+x=32-x | | 9x-x=40 | | 5x+2(x+8)-6(4x-5)= | | -3x^2+7x=-10 |